USING WORKSHEETS TO TEACH ENGLISH SPEAKING SKILL - Widiani Trisnaningsih (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2015)
AbstractThis research aimed at analyzing 1) effectiveness of using students’ worksheets in increasing English speaking skill; and 2) efficiency of using worksheets in speaking instruction. It was a quantitative research using quasi experimental non equivalent control group design. The sampling method was non probability sampling using purposive sampling. The instruments used were speaking test to analyze the students’ speaking skill, or the effectiveness of using worksheet on the other words; and questionnaire to analyze the efficiency in terms of students’ learning result, learning effort, and teaching time. The findings showed that the worksheets were effective in increasing students’ speaking skill (0.00 < 0.05). The effectiveness was seen from both linguistic aspects (ideas, pronunciation, vocabularies, and grammar) and sosiolinguistic aspects. The use of worksheets was also found efficient in increasing learning result, learning effort, and the use of instruction time. Needless to say, there are still some suggestions need considering for better treatment in the future.Key words: worksheets, speaking skill, learning effectiveness, learning efficiency.